Pharmacological and combined interventions for the acute depressive episode: focus on efficacy and tolerability - Andre R Brunoni; Renerio Fraguas Jr; Felipe Fregni (Dove Medical Press, 2009)
Andre R Brunoni1, Renerio Fraguas Jr1, Felipe Fregni21Department and Institute of Psychiatry, University of Sao Paulo, Brazil; 2Laboratory of Neuromodulation, Spaulding Rehabilitation Center, Harvard Medical School and Berenson-Allen Center for Noninvasive Brain Stimulation, Beth Israel Deaconess Medical Center, Harvard Medical School, Boston, USABackground: Use of antidepressants is the gold standard therapy for major depression. However, despite the large number of commercially available antidepressant drugs there are several differences among them in efficacy, tolerability, and cost-effectiveness. In addition the optimal augmentation strategy is still not clear when dealing with treatment-resistant depression, a condition that affects 15% to 40% of depressed patients.Methods: We therefore reviewed the main characteristics of these drugs regarding their efficacy, tolerability, side effects and cost-effectiveness, by accessing all meta-analyses and systematic reviews published from 2004 to 2009. In addition, we reviewed the augmentation strategy of associated antidepressants with neurostimulation therapies (such as transcranial magnetic stimulation [TMS] and transcranial direct current stimulation [tDCS]). A search was undertaken in MEDLINE, Web of Science, Cochrane, and Scielo databases. We included: 21 meta-analyses of antidepressant trials, 15 neurostimulation clinical trials and 8 studies of pharmacoeconomics. We then performed a comprehensive review on these articles.Results and Conclusion: Although recent meta-analyses suggest sertraline and escitalopram might have increased efficacy/tolerability, other studies and large pragmatic trials have not found these to be superior to other antidepressant drugs. Also, we did not identify any superior drug in terms of cost-effectiveness due to the different designs observed among pharmacoecomics studies. Side effects such as sexual dysfunction, gastrointestinal problems and weight gain were common causes of discontinuation. Tolerability was an important issue for novel neurostimulation interventions, such as TMS and tDCS. These therapies might be interesting augmentation strategies, considering their benign profile of side effects, if proper safety parameters are adopted.Keywords: acute depressive episode, pharmacological interventions, combined interventions